Music, thought, and feeling : understanding the psychology of music - Thompson, William Forde; Oxford University Press (Oxford ; New York : Oxford University Press, 2009)
From the Publisher: Examining the intersection of music, psychology, and neuroscience, Music, Thought, and Feeling surveys the rapidly growing field of music cognition and explores its most interesting questions. Written in clear, engaging language that balances scientific and artistic perspectives, this book provides an excellent introduction to-and critical analysis of-the major issues in music cognition, making it ideal for courses in psychology of music. Assuming minimal background in music or psychology, the book begins with an overview of the major theories on how and when music became a widespread aspect of human behavior. It also covers: How humans perceive music; Links between music and emotion; Modern neuroimaging techniques and what they tell us about music's effect on the brain; Psychological processes involved in imagining, composing, and performing music; Potential cognitive benefits of musical engagement. Music, Thought, and Feeling references numerous "Sound Examples" and is supplemented by a companion website (www.oup.com/us/Thompson) containing an extensive collection of music sample audio files, most created specifically for this book. In addition, the website provides a link to iTunes, where readers can access an iMix created to accompany the book
-- Preface -- 1: Introduction -- Learning outcomes -- Overview of book contents -- Abiding controversies -- Recent areas of research growth -- Additional readings -- 2: Origins Of Music -- Learning outcomes -- Prehistoric music -- Adaptationist accounts -- Theories based on reproductive benefits -- Theories based on survival benefits -- Nonadaptationist accounts -- Precursors to music -- Additional readings -- 3: Musical Building Blocks -- Learning outcomes -- Elements of sound -- Periodic motion -- Discovery of music within sound -- Sensory consonance and dissonance -- Tuning systems -- Sensitivity to pitch -- Models of pitch perception -- Absolute pitch -- Timbre -- Reconstructing music -- Additional readings -- 4: Music Acquisition -- Learning outcomes -- Musical infants -- Music in the womb -- Investigating music perception among infants -- Melodic contour -- Consonance and dissonance -- Pitch relations -- Scale structure -- Phrase structure -- Harmony -- Key -- Rhythm -- Memory for music -- Learning and enculturation -- Additional readings -- 5: Perceiving Music Structure -- Learning outcomes -- Arrangements of sounds -- Relative pitch -- Melodic contour -- Scale structure -- Large-scale structure -- Melodic expectancies -- Implicit memory for music -- Implied harmony -- Musical key -- Implied key -- Rhythm -- Additional readings -- 6: Music And Emotion -- Learning outcomes -- Emotion work -- Emotion and cognition -- Theories of music and emotion -- Empirical studies -- Do listeners agree on the emotional meaning of music? -- How do listeners respond emotionally to music? -- Compositional and expressive signals of emotion -- What properties of music lead to an emotional response? -- Is there a universal link between music and emotion? -- Sources of emotion in music -- Additional readings? -- 7: Music And The Brain -- Learning outcomes -- What's in a brain? -- Search for music inside the brain -- Neurological disorders -- Techniques of neuroimaging -- Neuroimaging and music -- Rapidly evolving field -- Additional readings -- 8: Performing Music -- Learning outcomes -- Playing music -- Acquiring performance skill -- Communicating musical structure -- Communicating emotional meaning -- Singing -- Improvising -- Gestures and facial expressions -- Evaluating performance -- Craft of the performer -- Additional readings -- 9: Composing Music -- Learning outcomes -- Radius of creativity -- Composers and listeners -- Cognitive constraints on composition -- Composing with multiple voices -- Where do new ideas come from? -- Craft of music composition -- Additional readings -- 10: Music And Other Abilities -- Learning outcomes -- Is music unique? -- Short-term effects of music -- Long-term benefits of music -- Educational implications -- Additional readings -- Glossary -- References -- Author index -- Subject index
Includes bibliographical references (pages 281-300) and index
Keywords: Music -- Psychological aspects; Musical perception; Cognition